Enhancing Problem-solving Skills Among Education Program Students Using EduwT@ps - Azmi, Norshima; Azid, Nurulwahida (International Journal of Psychosocial Rehabilitation, 2020)
Problem-solving skill is significant among the students of higher learning institutions to increase their employability rate. This study aims to enhance problem-solving skills among the students of education program using the interactive Educational Workplace Thinking Styles and Problem Solving Stimulator (EduwT@ps). Case-based learning method is used in this application as a simulation of the actual situation at the workplace (education institutions). The cases are divided into five categories of problems at workplace. Students are to solve the workplace problems, based on Sternberg Mental Self-government theory which simultaneously enhances their problem solving skills. The study used quasi-experimental design and 70 education program students of the Universiti Utara Malaysia (Northern University of Malaysia) were selected through a purposive sampling method. The sample was divided into control group (n = 35) and experimental group (n = 35). This study involved mixed method approach for data collections. The instruments used were pre and post tests using Heppner and Petersen problem solving inventory (PSI) adapted by Soliman and interview protocols. The effectiveness of EduwT@ps was determined based on the pretests and posttests and the data was analyzed using two-way multivariate analysis of covariance (MANCOVA) via SPSS 23.0 software. The results of the data analysis indicated that the overall results of the MANCOVA tests and interviews have proven that self-regulatory learning strategies using the EduwT@ps interactive application could improve the mean score of the treatment group on problem solving skills, compared to the control group that underwent the discussion learning strategy using print modules.